Factors Influencing Early Health Facility Contact and Low Default Rate among New Sputum Smear Positive Tuberculosis Patients, India - Ashok Kumar Bhardwaj; Surender Kashyap; Pradeep Bansal; Dinesh Kumar; Sunil Kumar Raina; Vishav Chander; Sushant Sharma (Pulmonary Medicine)
Early case identification and prompt treatment of new sputum smear positive case are important to reduce the spread of tuberculosis (TB). Present study was planned to study the associated factors for duration to contact the health facility since appearance of symptoms and treatment default. Methodology. It was prospective cohort study of TB patients already registered for treatment in randomly selected TB units (TUs) in Himachal Pradesh, India. Relative risk (RR) was calculated as risk estimate to find out the explanatory variables for early contact and default. Results. Total 1607 patients were recruited and 25 (1.5%) defaulted treatment. Patients from nuclear family (aRR: 1.37; 1.09–1.73), ashamed of TB (aRR: 1.32; 1.03–1.70), wishing to disclose disease status (aRR: 1.79; 1.43–2.24), but aware of curable nature (aRR: 1.67; 1.17–2.39) and preventable (aRR: 1.35; 1.07–1.70) nature of disease, contacted health facility early since appearance of symptoms. Conclusion. Better awareness and less misconceptions about disease influences the early contact of health facility and low default rate in North India.